Harmonizing Traditional Values in Modern Education - Hanaris, Fitria; Shobri, Ach.; Bakhtiyar Kizi , Nasiba Mirzayeva (Molang: Journal Islamic Education, 2023)
This study aims to explore the integration of traditional principles in the curriculum of Madrasah Ibtidaiyah Negeri (MIN) 2 Pamekasan. In order to achieve this goal, this research utilizes a qualitative approach with a case study type. Data collection techniques involve a series of procedures that include interviews, observations, and documentation. The data analysis technique used in this research is the data analysis technique from Miles and Huberman, by doing four ways, namely reducing data, presenting data, presenting data and drawing conclusions. The results of this study make a significant contribution in designing a future hybrid education model. This model is rooted in traditional values, yet remains relevant to the demands of modern times. Thus, this research proves that modern education and traditional values can go hand in hand. This allows the younger generation to understand and appreciate their cultural heritage, while remaining prepared for the challenges of the future. This research is expected to provide new and valuable insights for educational practitioners and researchers in the same field. As such, this study has the potential to enrich academic literature and educational practice.